Medical Students Training In Community Settings: An Essential Requirement To Meet Growing Health Needs Of Pakistani Population - Sara Shakil (Journal of Bahria University Medical and Dental College)
The successful provision of adequate primary health care delivery for the underprivileged population in the Asian subcontinent has remained a pressing issue over quite some time. Major reforms in health professions education have taken place across the globe including Asia. Unfortunately, the health education system implemented in Southern Asia (including Pakistan, India, Bangladesh etc.) has not been able to decrease morbidity and decrease the figures of adult and infant mortality rates in this region1.